Reward-related Brain Response and Craving Correlates of Marijuana Cue Exposure: A Preliminary Study in Treatment-Seeking Marijuana-Dependent Subjects - Goldman, Marina (2013)
OBJECTIVE: Determining the brain substrates underlying the motivation to abuse addictive drugs is critical for understanding and treating addictive disorders. Laboratory neuroimaging studies have demonstrated differential activation of limbic and motivational circuitry [e.g., amygdala, hippocampus, ventral striatum, insula, and orbitofrontal cortex (OFC)] triggered by cocaine, heroin, nicotine, and alcohol cues. The literature on neural responses to marijuana cues is sparse. Thus, the goals of this study were to characterize the brain’s response to marijuana cues, a major motivator underlying drug use and relapse, and determine whether these responses are linked to self-reported craving in a clinically relevant population of treatment-seeking marijuana-dependent subjects. METHODS: Marijuana craving was assessed in 12 marijuana-dependent subjects using the Marijuana Craving Questionnaire-Short Form. Subsequently, BOLD functional MRI data were acquired during exposure to alternating 20 second blocks of marijuana-related versus matched nondrug visual cues. RESULTS: Brain activation during marijuana cue exposure was significantly greater in bilateral amygdala and hippocampus. Significant positive correlations between craving scores and brain activation were found in ventral striatum, and medial and lateral OFC (p<0.0001). CONCLUSIONS: This study presents direct evidence for a link between reward-relevant brain responses to marijuana cues and craving, and extends the current literature on marijuana cue reactivity. Further, the correlative relationship between craving and brain activity in reward-related regions was observed in a clinically relevant sample (treatment-seeking marijuana-dependent subjects). Results are consistent with prior findings in cocaine, heroin, nicotine, and alcohol cue studies, indicating that the brain substrates of cue-triggered drug motivation are shared across abused substances.